2020
DOI: 10.1097/md.0000000000021668
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of different teaching methods on medical or nursing students

Abstract: Background: One of the major challenges in nursing and medical education is to foster the critical thinking ability and autonomous learning ability for students. But the effect of different teaching methods on these abilities of nursing or medical students has not been conclusive, and few studies have directly compared the differences in the effects of different teaching methods. As a result, it is necessary for students to evaluate the impact of different teaching methods on critical thinking abi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 25 publications
(21 reference statements)
0
3
0
1
Order By: Relevance
“…Developing countries' universities should adopt and adapt active teaching methods to improve nursing education by utilizing available resources. 29,30 The use of different active learning methods, especially, simulation pedagogy may improve communication and critical thinking skills and enhance safety in healthcare for the patients and nursing students themselves. 31 The research results indicated that one of the challenges was the lack of knowledgeable and skilful lecturers in the field of HAIs-PC education.…”
Section: Discussionmentioning
confidence: 99%
“…Developing countries' universities should adopt and adapt active teaching methods to improve nursing education by utilizing available resources. 29,30 The use of different active learning methods, especially, simulation pedagogy may improve communication and critical thinking skills and enhance safety in healthcare for the patients and nursing students themselves. 31 The research results indicated that one of the challenges was the lack of knowledgeable and skilful lecturers in the field of HAIs-PC education.…”
Section: Discussionmentioning
confidence: 99%
“…Nesse contexto, as metodologias ativas de ensino-aprendizagem têm sido utilizadas para formação e capacitação em saúde 7 , com inserção nos cursos de graduação em enfermagem, gerando, como aspectos positivos, maior motivação, interesse e envolvimento dos alunos, conclusão de estudos mais rápidos e com menor taxa de evasão, maior retenção de conhecimento, desenvolvimento de habilidades e competências profissionais e conexão mais sólida entre teoria e prática, integrando o conhecimento de diferentes disciplinas 10 .…”
Section: Discussionunclassified
“…"English Curriculum Standards" pointed out that it is the teaching process that allows students to develop their abilities in an all-round way and teachers to get feedback from students in a timely manner and promote it (Ministry of Education of the People's Republic of China, 2003;Yun et al, 2020). In the evaluation of other methods in the process of English teaching, it can make a judgment on the learning attitude, interest, and English ability of students and promote the enthusiasm of students (Hu & Yang, 2022).…”
Section: Evaluation Of English Classroom Teachingmentioning
confidence: 99%